Traumatic knife injury portal vein and common bile duct - Risi, Leonardo; Mori, Raúl; Miegges, Laura; Estefan, Alberto (Cirugía del Uruguay, 1996)
A report is presented of a case of traumatic lesion trom stabbing of the hepatic pedicle, Jesion of the portal ve_in and of the common bi/e duct. The lesion of the portal vein was so/ved by means of venoraphy and that of the principal bile way through a hepatic Jejunostomy calibrated by a transhepatic tube in seton. We have not found the latter procedure dealt with by the literature consulted.